2022
DOI: 10.3390/coatings12040494
|View full text |Cite
|
Sign up to set email alerts
|

Application of Chitosan-Lignosulfonate Composite Coating Film in Grape Preservation and Study on the Difference in Metabolites in Fruit Wine

Abstract: In order to solve the global problem of fruit rotting due to microbial infection and water loss after harvest, which leads to a large amount of food waste, this experiment uses degradable biological composite coating to prolong the preservation period of grapes. Chitosan (CH) and Lignosulfonate (LS) were used as Bio-based film materials, CH films, 1% CH/LS films and 2% CH/LS biomass composite films were synthesized by the classical casting method and applied to grape preservation packaging. Its preservation ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Phenolic acids provide precursor substrates for the synthesis of SPP and lignin, which provide important waterproofing properties and a protective barrier against pathogen infection in the periderm of potato tubers [36]. It has been shown that chitosan treatment can enhance fruit resistance by activating the activity of defense enzymes related to the lignin synthesis pathway [15,16,24], promote lignin synthesis and prolong fruit shelf life in citrus [37,38], pears [39], grapes [40], muskmelons [16] and bamboo shoots [41]. These effects occurred during the foliar spraying of chitosan in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Phenolic acids provide precursor substrates for the synthesis of SPP and lignin, which provide important waterproofing properties and a protective barrier against pathogen infection in the periderm of potato tubers [36]. It has been shown that chitosan treatment can enhance fruit resistance by activating the activity of defense enzymes related to the lignin synthesis pathway [15,16,24], promote lignin synthesis and prolong fruit shelf life in citrus [37,38], pears [39], grapes [40], muskmelons [16] and bamboo shoots [41]. These effects occurred during the foliar spraying of chitosan in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The chemical reactivity of the obtained lignosulfonate varies in accordance with the used hydroxide—ammonium lignosulfonate is the most active, whereas lignosulfonates obtained using calcium hydroxide are characterized by the least chemical reactivity [ 16 ]. Lignosulfonates have found their application in catalysis [ 17 , 18 ], as surfactants in oil recovery [ 19 ], in blends with chitosan to form coatings [ 20 ], and in the manufacturing of spherical micelles [ 21 ].…”
Section: Introductionmentioning
confidence: 99%